Single and co-breeding of different mosquito species in fogging-free and dengue risk areas in west Malaysia - Wan-Norafikah, Othman; Chen, Chee Dhang; Mohd-Amir, M.H.; Azahari, Abdul Hadi; Zainal Abidin, A.H.; Nazni, Wasi Ahmad; Mariam, M.; Mohd-Shahizan, J.; Sofian-Azirun, Mohd (Malaysian Society of Parasitology and Tropical Medicine, 2018)
Ovitrap surveillance was carried out in fifteen localities encompassing fogging-free and dengue risk areas in West Malaysia to determine on the dispersal and prevalence of single and co-breeding of mosquito larvae particularly Aedes. Ovitraps were sited randomly indoors and outdoors within human settlements in all study areas. All the localities exhibited positive ovitraps with single breeding of Ae. albopictus that ranged between 64.29% and 100.00%. These findings indicated Ae. albopictus as the predominant container-breeding species in all study areas. The co-breeding of Ae. aegypti with Ae. albopictus larvae (34 ovitraps), Ae. albopictus with Culex quinquefasciatus larvae (32 ovitraps) as well as Cx. quinquefasciatus with Armigeres subalbatus larvae (1 ovitrap) were also detected in certain study localities. Interestingly, co-breeding of Ae. albopictus with Ar. subalbatus larvae as well as Ae. albopictus with Uranotaenia sp. larvae in Malaysia is reported for the first time in the present study. Better understanding of the co-breeding scenario involving different species of mosquito larvae is needed to ensure the efficacy of vector control actions to be conducted.